Burden of Rotavirus Disease: A Population-Based Study in Eastern Townships, Quebec - Sylvain Bernard; Louis Valiquette; Philippe De Wals; Vincent Nault; Corentin Babakissa; Claude Cyr; Thérèse Côté Boileau; Arnaud Gagneur (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Since July 2010, the National Advisory Committee on Immunization of Canada has recommended rotavirus vaccination for all healthy infants. However, before implementing this vaccine in routine health programs, Canadian provinces need to establish current epidemiological data on rotavirus-associated acute gastroenteritis (AGE).